Abstract 225: Rescue Stenting for Posterior Circulation Strokes - Aaron Brake; Emmanuel Danso; Lane Fry; William Liu; Nathan Dougherty; Vince Galate; Michael Abraham (Stroke: Vascular and Interventional Neurology)
Introduction Intracranial atherosclerotic disease (ICAD) is associated with up to 32% of posterior circulation strokes.1 ICAD‐related strokes are at high risk for re‐occlusion following MT. Rescue treatment with stenting, balloon angioplasty, and/or intraarterial thrombolysis or antiplatelets are often required to treat the underlying stenosis. However, these rescue treatments are associated with their own risks.2,3 The SAMMPRIS trial reported that percutaneous transluminal angioplasty and stenting (PTAS) was associated with inferior outcomes compared to aggressive medical management alone but it is unclear whether these findings are generalizable to LVO strokes.4 Recent literature has reported clinical benefits associated with rescue stenting in the setting of ICAD‐related MT‐refractory strokes.5 However, most of the existing literature focuses on anterior circulation. This meta‐analysis aims to analyze the literature regarding the efficacy and safety of post‐thrombectomy PTAS in ICAD‐related posterior circulation strokes. Methods The search strategy was developed following the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines.6 Using the common evidence medicine framework PICOS (Patient Population, Intervention, Control/Comparison, Outcome, and Study type), we specified our research question: “In patients with posterior circulation AIS who underwent endovascular thrombectomy but failed to recanalize or who had severe stenosis, is PTAS an effective and safe rescue treatment option?” An electronic search of PubMed, EMBASE, Cochrane and OVID databases was performed from date of database inception to March 2023. Data was collected and analyzed using “Meta” package in RStudio.7 Outcomes of interest included 90 day modified Rankin score (mRS) and 90‐day mortality. Results A total of 10 studies were collected, but only 7 double‐arm studies involving 965 participants were included in this analysis. Among these patients, 544 underwent rescue stenting, while 421 were control patients. In a common effects meta‐analysis, patients who underwent stenting were more likely to have an mRS ≤ 2 at 90 days (OR 1.73, 95% CI [1.25 – 2.37]; p < 0.001) and lower odds of mortality at 90 days (OR 0.31, 95% CI [0.23 – 0.42]; p < 0.001). Additionally, patients undergoing stenting were less likely to have symptomatic intracranial hemorrhage (sICH) (OR 0.34, 95% CI [0.17 ‐ 0.67]; p = 0.002). Furthermore, the stenting group showed significantly higher odds of achieving a modified treatment in cerebral ischemia score (mTICI) of 2b‐3 when compared to the control group (OR 11.32, 95% CI [6.54 ‐ 19.59]; p < 0.001). Conclusion PTAS appears to be an effective and safe treatment for ICAD after MT in the posterior circulation both improving likelihood of good outcomes and overall survival. Given the uncertainty of applying the results of the SAMMPRIS trial to LVOs, further research is needed to better assess the efficacy and safety of PTAS in this patient population.